Anesthetic Risk in Cats Undergoing Surgical Procedures in a Veterinary Medical Teaching Hospital - Rodrigues, Nhirneyla Marques; Quessada, Ana Maria; Moraes, Aeyphanny Carlandy; Pereira, Cristian Francisco de Carvalho; Lima, Dayanne Anunciação Silva Dantas; Dantas, Sávio Soares Barbosa; Belettini, Salviano Tramontin; Silva, Filipi Alexandre do Nascimento (Acta Scientiae Veterinariae, 2018)
Background: To reduce morbidity and mortality associated with anesthetic procedures in cats, it is important to carry out a thorough pre-anesthetic evaluation. The surgical risk depends on several factors related to the patient, the surgical procedure, and the anesthetic used. Evaluation of perioperative mortality and the identification of the main factors of death reduce mortality rates. This research was conducted to evaluate and obtain the classification of physical status and anesthetic risk in cats submitted for surgical procedures. Materials, Methods & Results: Ninety-two cats were classified into anesthetic categories according to the American Society of Anesthesiologists (ASA) classification. The group consisted of 62 females (67.39%) and 30 males (32.61%). In the ASA classification, the emergency qualifier was added, resulting in 52.17% (48/92) of the total number of surgeries being considered as emergencies. The ASA I patients constituted the majority of the study sample (33.69%, 31/92). There were no deaths among ASA I patients. The ASA II patients represented 20.65% (19/92), with surgeries divided into non-emergency (42.10%, 8/19) and emergency (57.89%, 11/19). All ASA II patients had mild localized infections, and there were no deaths. ASA III patients constituted 28.26% (26/92) of the study sample and had moderate systemic alterations. Surgeries in this group were also classified as emergency (24/26, 92.30%) or non-emergency (2/26, 7.69%). There was one postoperative death in this group. The ASA IV patients represented 17.39% (16/92) of the study sample. The emergency surgeries (81.25%, 13/16) had a greater percentage than the elective surgeries. In this group, two deaths occurring in the immediate postoperative period. The overall mortality for the entire study sample was 3.26% (3/92). Discussion: The majority of the surgeries were emergency surgeries, indicating that, in the feline specie, in the service analyzed, most owners seek medical treatment under these conditions. In these situations, there is a need for rapid intervention since there is a high probability of immediate adverse consequences with the added risk of death. The results obtained from the ASA I patients are expected in animals of this classification, whose prognosis is considered excellent. The patients ASA II included six patients with obstructive lower urinary tract disease (OLUTD) that progressed to ASA III and IV, proving that patients with OLUTD need urgent attention. Some animals ASA III entered this classification because they presented anemia. These clinical sign was considered of great importance since the reduction of circulating red blood cells reduces tissue oxygenation, thereby increasing surgical risk due to hypovolemic shock. The one death in the ASA III group occurred in the postoperative period, and necropsy indicated septicemia, which has a high mortality rate. ASA IV patients were placed in this category due to serious diseases such as neoplasms accompanied by secondary infection, urolithiasis with post-renal azotemia, OLUTD with azotemia, and pyometra. All deaths in the ASA IV group occurred in the immediate postoperative period. Recent data suggest that the postoperative period is the period associated with the highest risk of mortality. This may have been a reason for these deaths, along with the fact that all these patients were emergency patients, because in such procedures, the risk of death is much higher in patients undergoing emergency surgeries than in those undergoing elective surgeries. Starting by the patients classified as ASA grade III, the mortality was higher, as well as in cases of emergency. The overall mortality rate was high, with a higher risk during the immediate postoperative period. It is recommended that felines be carefully monitored postoperatively to reduce mortality rates.